2017
DOI: 10.1016/j.micres.2017.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Improving gentamicin B and gentamicin C1a production by engineering the glycosyltransferases that transfer primary metabolites into secondary metabolites biosynthesis

Abstract: Gentamicin B and gentamicin C1a are the direct precursor for Isepamicin and Etimicin synthesis, respectively. Although producing strains have been improved for many years, both gentamicin B titer and gentamicin C1a titer in the fermentation are still low. Because all gentamicin components are biosynthesized using UDP-N-acetyl-d-glucosamine (UDP-GlcNAc) and UDP-xylose as precursors, we tried to explore strategies for development of strains capable of directing greater fluxes of these precursors into production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Our previous study also identified dozens of constitutive promoters that exhibited stronger activity than ermE* in Streptomyces (Liu et al., 2016). However, in previous work, there was no report on the determination of promoter strength in Micromonospora , and researchers could only roughly use hrdB and ermE* for gene overexpression (Ni et al., 2016; Wu et al., 2017). In this study, we tested these promoters’ strengths in Micromonospora by measuring the relative activity of the reporter gene gusA which was placed downstream of each candidate promoter to provide more selectable promoter elements for subsequent gene overexpression.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study also identified dozens of constitutive promoters that exhibited stronger activity than ermE* in Streptomyces (Liu et al., 2016). However, in previous work, there was no report on the determination of promoter strength in Micromonospora , and researchers could only roughly use hrdB and ermE* for gene overexpression (Ni et al., 2016; Wu et al., 2017). In this study, we tested these promoters’ strengths in Micromonospora by measuring the relative activity of the reporter gene gusA which was placed downstream of each candidate promoter to provide more selectable promoter elements for subsequent gene overexpression.…”
Section: Resultsmentioning
confidence: 99%
“…46). The substantial titer improvement of 1 with highly efficient heterologous G-1-PTs [31][32][33] further demonstrated that overexpression of enzymes that divert primary metabolites into secondary metabolism is a useful strategy 41 (Fig. 6e).…”
Section: Discussionmentioning
confidence: 92%
“…The industrial production of etimicin requires a significant quantity of high-purity gentamicin C1a. As a result, many researchers have employed genetic engineering techniques to develop strains that produce high yields of single-component C1a [6,[19][20][21].…”
Section: Determination Of Sugar Amino Nitrogen Germ Concentration And...mentioning
confidence: 99%